2017
DOI: 10.1007/s10554-017-1219-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of myocardial iron overload by two-dimensional speckle tracking in patients with beta-thalassaemia major: a combined echocardiographic and T2* segmental CMR study

Abstract: We aimed to evaluate the role of two-dimensional speckle tracking imaging (2DSTI) in detecting early changes of myocardial deformation in patients affected by thalassemia major (TM) and its relation with myocardial iron overload (MIO) detected by T2* cardiovascular magnetic resonance (CMR). We studied 28 TM patients (15 males, 37.4 ± 10 years). All patients underwent CMR and echocardiography in the same day. Segmental and global T2* values were measured. Values of global longitudinal strain (GLS) were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Lastly, for studies including iron overload patients most T 2 * measurements were performed in the intraventricular septum for reproducibility, because the lateral wall often contains dephasing artefacts. Nevertheless, some studies reported an average of the mid-ventricular SAx slice [87,115,119,134] or the entire myocardium [106,125,[127][128][129][130][131][132], which especially on 3 T [127] could lead to some unrealistic T 2 * values due to aforementioned artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, for studies including iron overload patients most T 2 * measurements were performed in the intraventricular septum for reproducibility, because the lateral wall often contains dephasing artefacts. Nevertheless, some studies reported an average of the mid-ventricular SAx slice [87,115,119,134] or the entire myocardium [106,125,[127][128][129][130][131][132], which especially on 3 T [127] could lead to some unrealistic T 2 * values due to aforementioned artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended to use midventricular septum as a comparatively artifact‐free region to measure iron overload 31 . The postmortem finding showed that iron distribution is heterogeneous in the myocardium, as reported using the global longitudinal strain method, 43 and was confirmed by the T 2 * measurements in global myocardium 19–21,25,27,41,43,45,49,57–59 . Different iron overload patterns in different myocardial segments beyond the influence of susceptibility artifact were observed.…”
Section: T2* Mapping Techniquesmentioning
confidence: 60%
“…4). 25,43,46,57 Iron distribution identification in postmortem heart samples with severe iron overload revealed higher iron concentration in the epicardial than in the endocardial region 10,11,13 . It has been recommended to use midventricular septum as a comparatively artifact‐free region to measure iron overload 31 .…”
Section: T2* Mapping Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] HTN induces myocardial inflammation, fibrosis, vascular and myocardial remodeling. 4,5 A paramagnetic effect can be observed by the iron deposits (e.g., intramyocardial hemorrhage of myocardial infarction, 6,7 iron overload of hemochromatosis and thalassemia, [8][9][10] and the net or relative increase of deoxygenated hemoglobin [compared with oxygenated hemoglobin] in the capillary blood, which ultimately shortens the T2* relaxation times, measured using BOLD (blood oxygen level dependent) MRI. 11,12 BOLD MRI can detect regional condition of myocardial oxygen supply and demand by means of paramagnetic properties.…”
mentioning
confidence: 99%